Histological Features of Catecholaminergic Neuron in Substantia Nigra Induced by Paraquat Dichloride (1,1-dimethyl-4,4 bipyridinium) in Wistar Rat as A Model of Parkinson Disease - Tri Wahyu Pangestiningsih; Woro Danur Wendo; Yulfia Nelymalik Selan; Filphin Adolfin Amalo; Nemay Anggadewi Ndaong; Victor Lenda (Universitas Gadjah Mada, 2014)
Paraquat dichloride has been used by farmers as a herbicide to kill the grass. On the other hand, paraquatdichloride is harmful if enters to the body, causing Parkinson’s disease, since it is disrupting dopamineproduction in the substantia nigra pars compacta or dopamine pathways Nigro striatal pathway. The studywas done to fi nd out the histological changes of catecholaminergic neurons and Nigro striatal pathway causedby paraquat dichloride treatment in Wistar rats as a model of Parkinson’s disease.Twenty-two Wistar rats 3,5 months old were divided into 4 groups, 5 rats each. Group I (control group)were injected with aquabidest, while groups II, III, and IV were injected intraperitoneally with paraquatdichloride in aquabidest, with the dosage 5 , 10 and 15 mg/kg bw respectively. The rats were injected onceper week for 6 weeks. Three days after the last injection, the rats were anesthetized using xylasin (2 mg/kg)and ketamine (20 mg/kg) intramuscularly, and then were intracardiac perfused using physiological saline asprerinse solution, followed by 10% buffered formalin solution as a fi xative. After animals were fi xed, the brainswere removed and embedded in paraffi n block and cut in 12 μm thickness for immunohistochemistry stainingusing tyrosine hydroxylase antibody. The results of staining then were observed under light microscope andanalyzed descriptively.The results showed that the catecholaminergic neurons were distributed in the substantia nigrapars compacta in all treatment groups, however, the cell density were found decreased only in group IV.Catecholaminergic neurons appear in the bipolar and multipolar form, while dopamine ‘Nigro striatal pathway’was found exist in all treatment groups. From our study, histologycally the decreased of catecholaminergicneurons is only found in rats that received paraquat dichloride in dose 15 mg/kg bw for 6 weeks.